Teacher Professionalism in Islamic Religious Education During The Covid 19 Pandemic At Baitul A'la Islamic Primary School in Lubuklinggau - Fitriyani, Fitriyani; Sari, Desi Solema; Mukmin, Taufik; Erlindawati, Erlindawati (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
This study is titled Teacher Professionalism in Islamic Religious Education during the Covid19 Pandemic at Baitul A'la Islamic Primary School in Lubuklinggau. The adoption of e-learning certainly requires teachers to be professional in performing their tasks and preparing for different sections. The research was carried out at Baitul A'la Islamic Primary School in Lubuklinggau using field research type, qualitative approach, data collection with interview, observation and documentation techniques. Check data source reliability, triangle processing time and technique. To summarize, first, teachers are committed to students and their learning process, teachers are masters of subject topics, teachers monitor student learning outcomes, teachers are able to systematically and teachers are part of a learning community in their professional setting. Online learning, which schools have had to do due to the COVID19 outbreak, needs to be balanced with the deeper role of the teacher. Teacher performance is required as a form of professionalism. Therefore, there is a need to empower teachers by developing four key skills that already exist to deal with online learning today. The skills that emerged from these developments were literacy and science and technology skills, classroom management skills, and social and communication skills.